2006
DOI: 10.2519/jospt.2006.2208
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Prediction Rule for Classifying Patients With Patellofemoral Pain Syndrome Who Respond to Patellar Taping

Abstract: Study Design: Predictive validity/diagnostic test study. Objective: To determine the predictive validity and interrater reliability of selected clinical exam items and to develop a clinical prediction rule (CPR) to determine which patients respond successfully to patellar taping. Background: Patellar taping is often used to treat patients with PFPS. However, the characteristics of the patients who respond best to patellar taping intervention have not been identified. Methods and Measures: Fifty volunteers (27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 67 publications
1
23
1
Order By: Relevance
“…Importantly, in terms of reliability, the measurements of medial/lateral position were performed on a single patella. This reduces the strength of the study's findings when compared to those of Fitzgerald and McClure, 22 Tomisch et al, 94 and Watson et al, 102 who assessed the intertester reliability of measurements of mediolateral patellar position on 66, 27, and 101 knees, respectively, and Lesher et al, 52 who examined patellar orientation on 50 knees. Also, the intertester reliability of the MRI measure in Herrington's 32 study was untested, as was the intratester reliability of the clinical measures.…”
Section: Clinical Measurements Of Patellar Alignment Patellar Orientamentioning
confidence: 58%
See 1 more Smart Citation
“…Importantly, in terms of reliability, the measurements of medial/lateral position were performed on a single patella. This reduces the strength of the study's findings when compared to those of Fitzgerald and McClure, 22 Tomisch et al, 94 and Watson et al, 102 who assessed the intertester reliability of measurements of mediolateral patellar position on 66, 27, and 101 knees, respectively, and Lesher et al, 52 who examined patellar orientation on 50 knees. Also, the intertester reliability of the MRI measure in Herrington's 32 study was untested, as was the intratester reliability of the clinical measures.…”
Section: Clinical Measurements Of Patellar Alignment Patellar Orientamentioning
confidence: 58%
“…They concluded that both visual estimation and instrumented measurements of patellar orientation produced results that were clinically unacceptable and unreliable. In a recent study, Lesher et al 52 examined the intertester reliability of a battery of orthopaedic tests, including patellar orientation, performed on 50 patients with PFPS by 2 testers. Patellar orientation was visually estimated and categorized as medial, neutral, or lateral.…”
Section: Clinical Measurements Of Patellar Alignment Patellar Orientamentioning
confidence: 99%
“…3 With respect to reliability, several investigations have assessed the interrater reliability of the clinical test for femoral anteversion. 10,14,15,19,23,24 The results of these studies vary considerably, as illustrated by the wide range of reported reliability coefficients (0.17-0.97) and measurement error (1.1°-8.4°). Of these studies, only 1 investigated intrarater reliability of the clinical test for femoral anteversion.…”
Section: Instrumentationmentioning
confidence: 99%
“…Th e rules are algorithmic in nature and involve condensed information that identifi es the smallest number of indicators that are statistically diagnostic to the targeted condition 6 . Th e number of derived or validated CPRs is increasing 6 , specifi cally in rehabilitation medicine where prescriptive studies have been developed for musculoskeletal interventions for low back pain 7,8 , cervical pain 9,10 , and knee dysfunction 11,12 . Clinical prediction rules may best be classifi ed into three distinct groups: 1) diagnostic, 2) prognostic, and 3) prescriptive 1,13 .…”
Section: What Are Clinical Prediction Rules?mentioning
confidence: 99%